Kualitas Produk Sumpit Dari Limbah Kayu Pada UD. Akselerasi Palangka Raya : Quality of Chopstick Products Made from Wood Waste at UD. Akselerasi Palangka Raya - Nuwa, Nuwa; Nursiah, Nursiah; Octavianus, Robby; Augent, Ryandi (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
This study aims to determine the quality of chopstick products and to understand the objectives and quantity of products marketed by UD. Akselerasi. The research was conducted in the city of Palangkaraya. Data collection techniques in this study included interviews, observations, and documentation. The data analysis used a qualitative descriptive analysis technique. There are several steps in analyzing the data: data reduction, data presentation, and conclusion drawing. The results of this study show that the production process carried out by UD. Akselerasi maintains the quality of chopsticks through a strict series of processes, starting from the selection of raw materials to the finishing stage. White Meranti wood was chosen as the main material due to its suitability for chopstick production. Defective products are sorted and not shipped, and there is a replacement policy for products found to be defective after shipment. This reflects the company's commitment to quality and customer satisfaction. UD. Akselerasi primarily focuses on chopstick production, with 99% of the total production being exported to Japan. This demonstrates the company's specialization in meeting international market demand, particularly Japan, which is known for its high-quality standards. An effective marketing strategy through social media, exhibitions, and direct visits from buyers also supports strong international market penetration.